2006
DOI: 10.1016/j.clinph.2005.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Sources and effects of electrode impedance during deep brain stimulation

Abstract: Objective-Clinical impedance measurements for deep brain stimulation (DBS) electrodes in human patients are normally in the range 500-1500 Ω. DBS devices utilize voltage-controlled stimulation; therefore, the current delivered to the tissue is inversely proportional to the impedance. The goals of this study were to evaluate the effects of various electrical properties of the tissue medium and electrode-tissue interface on the impedance and to determine the impact of clinically relevant impedance variability on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
291
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 320 publications
(302 citation statements)
references
References 29 publications
(46 reference statements)
7
291
3
1
Order By: Relevance
“…The distribution of the electric potential in the vicinity of a DBS electrode has previously been modelled using isotropic homogenous tissue [8][9][10][11][12][13][14][15][16]. More recently, Butson et al [17] presented a three dimensional (3D) patient-specific method to predict the volume of tissue activated by DBS based on diffusion tensor images (DTI).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of the electric potential in the vicinity of a DBS electrode has previously been modelled using isotropic homogenous tissue [8][9][10][11][12][13][14][15][16]. More recently, Butson et al [17] presented a three dimensional (3D) patient-specific method to predict the volume of tissue activated by DBS based on diffusion tensor images (DTI).…”
Section: Introductionmentioning
confidence: 99%
“…Neural activation thresholds were calculated using a previously published field-neuron simulation model (Butson et al, 2006a) (Figure 1C). Briefly, a finite element electric field model was used to calculate the voltage distribution surrounding the DBS electrode as a function of stimulation parameters.…”
Section: Methodsmentioning
confidence: 99%
“…The model included the capacitance of the electrode-tissue interface, which causes a voltage decay in the plateau phase of the stimulus waveform (Butson and McIntyre, 2005). The model also included explicit representation of the encapsulation tissue that surrounds the electrode, which is correlated with electrode impedance (Butson et al, 2006a). Both the electrode capacitance and the encapsulation layer cause increased threshold voltages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factors influencing SUA recordings are the diameter and the impedance of the electrode. The relationship between the size of the electrode surface and the impedance is inversely proportional, with electrodes with larger area exhibiting lower impedance (Butson et al, 2006;Ludwig et al, 2006). Prasad et al found that the ideal resistance for SUA detection is between 40-150kΩ (Prasad and Sanchez, 2012).…”
Section: Sensors Recording Neuronal Activitymentioning
confidence: 99%